Effect of Helicobacter pylori eradication on development of dyspeptic and reflux disease in healthy asymptomatic subjects - Vaira, D (Copyright 2003 by Gut, 2003)
Background and aim: There are few data on the course of Helicobacter pylori infection in asymptomatic subjects. The aim of this study was to assess the effect of eradication therapy on the development of dyspeptic and gastro-oesophageal reflux disease in a cohort of asymptomatic individuals observed over a prolonged period. Methods: A total of 169 blood donors infected with H pylori who had volunteered for studies on eradication in 1990 formed the cohort. To be included in this cohort subjects had to have no symptoms, as determined by a validated symptom questionnaire at the baseline visit. Eighty eight subjects were infected with H pylori while 81 had successfully undergone eradication therapy. Subjects were followed up (annually) using the same symptom questionnaire and in 2000 they underwent repeat endoscopy. Results: Thirteen subjects developed symptoms during follow up. The incidence of symptoms in H pylori positive subjects was 1.893/100 person-years of follow up and in H pylori negative individuals 0.163/100 person-years of follow up. H pylori infected subjects were significantly more likely to develop symptoms (log rank test, p=0.003) as well as those infected with CagA positive strains (log rank test, p=0.017). The development of symptomatic gastro-oesophageal reflux disease was no different in individuals with and without eradication (odds ratio 0.57 (95% confidence interval 0.26–1.24); p=0.163). Conclusions: H pylori eradication prevents the development of dyspeptic symptoms and peptic ulcer disease in healthy asymptomatic blood donors and is not associated with an increase in the incidence of symptomatic gastro-oesophageal reflux disease.